Relationship between Temporomandibular Disorder and Quality of Sleep in a Sample of Nurses in a Type C Private Hospital in Depok, West Java, Indonesia - Maxwell, David; Amalina, Fadhillah Nur; Tanti, Ira (Journal of Dentistry Indonesia, 2018)
Temporomandibular disorder can affect the quality of sleep. Objective: To analyze the association between temporomandibular disorder and quality of sleep among nurses in a type C private hospital using the ID-TMD and PSQI Indonesian version questionnaire. Methods: This cross-sectional study assessed the data of 92 nurses in Hasanah Graha Afiah Hospital, Depok City, West Java, Indonesia. Three questionnaires were administered to each hospital nurse. The ID-TMD questionnaire was used to evaluate temporomandibular disorder; the PSQI Indonesian version was used to evaluate quality of sleep. Results: T he results showed significant differences between temporomandibular disorder and quality of sleep among nurses in a type C private hospital (p = 0.02). Conclusion: There was a relationship found in this study between temporomandibular joint disorder and quality of sleep in a type C private hospital.